Formação dos coordenadores pedagógicos em Boa Vista do Tupim/BA: uma experiência colaborativa, o fio por trás das missangas - Gouveia, Beatriz Bontempi (2012)
The objective of this study was to analyse the process for the creation of the training role of the educational coordinators working in the state primary schools network of the municipality of Boa Vista do Tupim, in Chapada Diamantina/BA. This municipality is part of Projeto Chapada, a program of Instituto Chapada de Educação e Pesquisa, a non-governmental organisation, which invests in the training of technical teams operating in the Municipal Education Departments, which in turn are responsible for training educational coordinators who work in schools. This study considers the training process for educational coordinators and their training requirements from the perspective of the coordinators and their trainers. The political efforts made by the municipality to implement an ongoing training structure, from the Department with its technical teams to the coordinator at schools, has achieved good results for the quality of learning of students and the professional development of teachers. An analysis of all the data collected (interviews, discussion group, observation of schools) revealed that the coordinators see training as their main function in schools. Thanks to political and technical support from the Municipal Education Department, they managed to create dedicated training spaces in the schools routines; and they recognise and value the presence of their trainers and the efforts to meet their training needs. The premise of the training network in the municipality of Boa Vista do Tupim is that it is not possible to improve the quality of state schools through isolated, external and individual training activities. On the contrary, the current system involves a series of interconnected actions, involving the different stakeholders in the educational sphere. The coordinators are responsible for teacher s training, but they cannot undertake this task alone. All parties involved in this training chain bear joint responsibility and offer training and technical support to the trainer within the network. The collaborative network is designed to serve as a foundation for training activities and as a space for democratic participation, horizontal relations and extensive partnerships. Understanding how the municipality of Boa Vista do Tupim managed to implement this process for successfully creating the training role of the coordinator will be a way in which this study can contribute to the area of educational coordination, the training of professionals and to education itself